Orthopaedic applications of cold physical plasma - Lars Nonnenmacher; Maximilian Fischer; Lyubomir Haralambiev; Sander Bekeschus; Frank Schulze; Georgi I Wassilew; Janosch Schoon; Johannes C Reichert (EFORT Open Reviews, 2023)
Cold physical plasma (CPP) technology is of high promise for various medical applications. The interplay of specific components of physical plasma with living cells, tissues and organs on a structural and functional level is of paramount interest with the aim to induce therapeutic effects in a controlled and replicable fashion. In contrast to other medical disciplines such as dermatology and oromaxillofacial surgery, research reports on CPP application in orthopaedics are scarce. The present implementation of CPP in orthopaedics involves surface modifications of orthopaedic materials and biomaterials to optimize osseointegration. In addition, the influence of CPP on musculoskeletal cells and tissues is a focus of research, including possible adverse reactions and side effects. Its bactericidal aspects make CPP an attractive supplement to current treatment regimens in case of microbial inflammations such as periprosthetic joint infections. Attributed anticancerogenic and pro-apoptotic effects underline the clinical relevance of CPP as an additive in treating malignant bone lesions. The present review outlines ongoing research in orthopaedics involving CPP; it distinguishes considerations for safe application and the need for more evidence-based research to facilitate robust clinical implementation.